Altering the rate-determining step over cobalt single clusters leading to highly efficient ammonia synthesis. Issue 5 (17th June 2020) - Liu, Sisi; Wang, Mengfan; Ji, Haoqing; Shen, Xiaowei; Yan, Chenglin; Qian, Tao
Abstract: Activation of high-energy triple-bonds of N2 is the most significant bottleneck of ammonia synthesis under ambient conditions. Here, by importing cobalt single clusters as strong electron-donating promoter into the catalyst, the rate-determining step of ammonia synthesis is altered to the subsequent proton addition so that the barrier of N2 dissociation can be successfully overcome. As revealed by density functional theory calculations, the N2 dissociation becomes exothermic over the cobalt single cluster upon the strong electron backdonation from metal to the N2 antibonding orbitals. The energy barrier of the positively shifted rate-determining step is also greatly reduced. At the same time, advanced sampling molecular dynamics simulations indicate a barrier-less process of the N2 approaching the active sites that greatly facilitates the mass transfer. With suitable thermodynamic and dynamic property, a high ammonia yield rate of 76.2 μg h –1  mg$^{-1 }_{\rm cat.}$ and superior Faradaic efficiency of 52.9% were simultaneously achieved. Abstract : The most significant bottleneck of ambient ammonia synthesis, namely nitrogen activation, has been successfully overcome by altering the rate-determining step over cobalt single clusters-contained electrocatalyst, and superior nitrogen reduction performance was achieved.